The impact of the COVID-19 pandemic on children's dental care in the Unique Health System of João Pessoa – PB (Research, Society and Development, 2021)
This study aimed to analyze the impact of the Sars-CoV-2 coronavirus pandemic on dental care for children and adolescents in the city of João Pessoa-PB. This is a temporal study carried out from September 2019 to 2020. Secondary public information was used for primary and secondary care services, characterized by oral health indicators which were obtained by SIA / SUS, a database of the Ministry of Health (DATASUS). In this study, dental care provided at SUS was considered in the semester that preceded the COVID-19 pandemic. During this period, 1,413 procedures were performed on children and adolescents in the greater João Pessoa. On average, 235.5 ± 85.3 monthly procedures are performed. In the first half of the new coronavirus pandemic, the number of procedures performed fell by 46.42%. 757 dental procedures were performed and in May, no procedures were performed in children and adolescents. Thus, we can conclude that there has been a significant reduction in the number of dental services, and this phenomenon can generate a significant pent-up demand in this audience. With that, we suggest studies to develop oral health promotion and prevention policies when collective care is normalized.